Role of Routine Breast-Self Examination for Cancer Screening - Hawar (Journal of Sulaimani Medical College, 2025)
Background: Breast self-examination (BSE) and screening mammography have been advocated as general screening methods to diagnose breast cancer (BC) at an early stage, thereby reducing morbidity and mortality. Objective: To determine the role of regular self-examination versus mammography for BC screening and which one is more likely reduces the morbidity and mortality rates. Patients and methods: A cross-sectional was conducted on 429 women at the Breast Diseases Treatment Clinic, Shar Teaching Hospital, Sulaimaniyah, Iraq, from January 2017 to December 2021. Women were provided with a validated questionnaire that inquired about their health, demographics, and overall awareness of the disease. Also, information regarding the clinicopathological characteristics of the tumor from the patient's medical records were obtained. Results: The participants' ages ranged from 24 to 85 years, with a mean of 49.6±11 years. Most women were middle-aged (53.8%), from urban areas (80.2%), illiterate (41.7%), married (86.5%), housewives (79.0%), and non-smokers (91.4%). There were highly significant correlations between mammography and tumor stage (p=0.016) with no significant relationship between BSE and tumor stage (p=0.982). Conclusions: The evidence regarding BSE is unequivocal; it offers no advantage in reducing BC mortality and indicates that it may be more detrimental than beneficial.
Keywords: Breast self-examination; breast cancer; mammography; tumour stage